Biomass of fifty conifer forests and nutrient exports associated with their harvest - Weaver, T.; Forcella, F. (My University, 1977)
Biomasses of climax Rocky Mountain forests studied ranged from less than 50 to more than 300 tons/ha. Total biomass was approximately 1.5 times the biomass of normally merchantable boles. When compared with conventional bole harvest, the nutrient exports associated with harvest of all aboveground parts in these stands would apparently be at least three times higher for nitrogen, six times higher for phosphorus, four times higher for potassium, and three times higher for calcium.